Modified lithium-rich manganese-based positive electrode material and preparation method thereof, and lithium-ion battery

Through co-precipitation method and the coating modification of the polyether polyurethane layer, the low efficiency and rate performance problems of lithium-rich manganese-based positive electrode materials are solved, significantly improving the lithium ion diffusion rate and electronic conductivity, and improving the electrochemical performance and Circulation performance has promoted its large-scale commercial application.

CN118588919BActive Publication Date: 2024-12-13GANZHOU NOVA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411080591.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-13
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

The first-time Coulombic efficiency of lithium-rich manganese-based cathode materials is low, and the rate performance is limited by the conductivity and ion diffusion kinetics of Li2MnO3, and the side reactions on the surface of the material increase the battery impedance, limiting its large-scale commercial application.

Method used

The hydroxide precursor prepared by co-precipitation method is mixed with the lithium source and sintered, combined with the coating modification of the polyether polyurethane layer, and the number of lithium ion diffusion channels and electron conductivity are improved through multi-element synergistic doping, thereby inhibiting side reactions and Transition metal dissolution.

Benefits of technology

It significantly improves the lithium ion diffusion rate and electronic conductivity of lithium-rich manganese-based positive electrode materials, improves electrochemical performance and cycling performance, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118588919B_ABST
    Figure CN118588919B_ABST
Patent Text Reader

Abstract

The present invention provides a modified lithium-rich manganese-based positive electrode material, comprising a lithium-rich manganese-based positive electrode material matrix and a polyether polyurethane layer on the surface of the lithium-rich manganese-based positive electrode material matrix. The lithium-rich manganese-based positive electrode material is doped with polyether polyurethane to significantly improve the electronic conductivity of the material, overcome the problem of irreversible loss of the first-cycle discharge capacity of the lithium-rich manganese-based positive electrode material, and can also stabilize the structure of the positive electrode material, inhibit side reactions and transition metal dissolution on the surface of the positive electrode material in the electrolyte, and improve the cycle performance of the battery. Also provided are a preparation method of the modified lithium-rich manganese-based positive electrode material and a lithium-ion battery based on the modified lithium-rich manganese-based positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to the modification of lithium-rich manganese-based positive electrode materials. Background Art

[0002] Lithium-ion batteries have the advantages of light weight, high energy density, long cycle life, no memory effect, and environmental friendliness. They are currently widely used in portable electronic products (such as mobile phones, digital cameras, and laptops), electric vehicles, and large energy storage grids. However, with the rapid development of lithium-ion battery applications, people have also put forward higher and higher requirements for its various performance indicators. Among them, the quality of the positive electrode material, as the key core part, directly determines the performance indicators of lithium-ion batteries.

[0003] Lithium-rich manganese-based cathode materials are solid solutions formed by layered LiMO2 (M = Ni, Co, Mn) and Li2MnO3 in different proportions. Compared with the currently widely used lithium cobalt oxide, lithium iron phosphate, and layered ternary cathode materials, lithium-rich manganese-based cathode materials have an abnormally high discharge specific capacity (>250mAh g -1 ) and energy density (>1000Wh kg -1 ), while reducing the cobalt content also reduces the overall cost of the battery manufacturing process. Driven by the demand for high energy density lithium-ion batteries, researchers are actively developing the next generation of lithium-rich layered oxide high specific capacity cathode materials. So far, lithium-rich manganese-based cathode materials have been applied to lithium batteries in small power, energy storage, digital and other fields. The penetration into the power field is accelerating, and many battery manufacturers and raw material manufacturers have listed lithium-rich manganese-based materials as one of their key research and development projects.

[0004] However, the large-scale commercial application of lithium-rich manganese-based cathode materials is still limited by many problems. For example, the first coulombic efficiency of lithium-rich manganese-based cathode materials is low. At the same time, the rate performance of lithium-rich manganese-based materials is largely limited by the Li2MnO3 component, because the conductivity of Li2MnO3 is low and the reaction kinetics of Mn are worse than those of Ni and Co. In addition, unlike the three-dimensional ion diffusion channels of the spinel structure, the Li ions in the lithium-rich manganese-based cathode only diffuse in a limited two-dimensional plane perpendicular to the (001) crystal plane, further limiting its intrinsic ionic conductivity. The dissolution of TM ions on the surface of the material and the side reactions of the electrolyte will also produce NiO-like rock salt harmful phases, which increase the battery impedance ratio and hinder the transmission of lithium ions.

[0005] Therefore, the modification of lithium-rich manganese-based cathode materials has important practical significance for promoting their large-scale commercial application. Summary of the invention

[0006] In response to at least one of the above technical problems, the present application provides a modified lithium-rich manganese-based positive electrode material and a preparation method thereof, and a lithium-ion battery.

[0007] To achieve the above objectives, this application proposes the following technical solutions:

[0008] In a first aspect, a modified lithium-rich manganese-based positive electrode material is provided, comprising a lithium-rich manganese-based positive electrode material matrix and a polyether polyurethane layer on the surface of the lithium-rich manganese-based positive electrode material matrix.

[0009] Furthermore, the chemical formula of the lithium-rich manganese-based positive electrode material matrix is ​​xLi2MnO3·(1-x)LiMn a Co b Ni c Zr d Nb e Mo f O2, where 0<x<1, a+b+c+d+e+f=1, 0.5≤a<1, 0≤b<0.5, 0≤c<0.5, 0≤d+e+f<0.02.

[0010] Furthermore, the lithium-rich manganese-based positive electrode material matrix is ​​prepared by a hydroxide precursor Mn a Co b Ni c Zr d Nb e Mo f It is obtained by mixing (OH)2 and a lithium source and sintering.

[0011] Furthermore, the polyether polyurethane layer is obtained by polymerizing low molecular weight ether oxygen polymer, isocyanate organic matter and polyol.

[0012] Furthermore, the mass of the polyether polyurethane layer is 0.1% to 1.5% of the lithium-rich manganese-based positive electrode material matrix.

[0013] In a second aspect, a method for preparing a modified lithium-rich manganese-based positive electrode material is provided, comprising:

[0014] S1, adding a lithium-rich manganese-based positive electrode material into an organic solvent and dispersing the material to obtain a dispersion;

[0015] S2. Add low molecular weight ether oxygen type polymer and isocyanate organic matter to the dispersion, add dibutyltin dilaurate catalyst after the added materials are dissolved, carry out a primary reaction, and then continue to add polyol to carry out a secondary polymerization reaction. After the reaction is completed, solid-liquid separation and drying are carried out to obtain a polyether polyurethane coated modified lithium manganese-rich positive electrode material.

[0016] Furthermore, the low molecular weight ether oxygen type polymer is one or more of polytetrahydrofuran, polyethylene oxide, and polypropylene oxide.

[0017] Furthermore, the isocyanate organic compound is one or more of hexamethylene diisocyanate, xylylene diisocyanate, and methylcyclohexylene diisocyanate.

[0018] Furthermore, the polyol is one or more of propylene glycol, 1.4-butanediol, and pentaerythritol.

[0019] Furthermore, the organic solvent is one of diethyl ether and acetone.

[0020] Furthermore, the molar ratio of the low molecular weight ether oxygen type polymer, the isocyanate organic matter and the polyol is 1:(2.2-2.5):1.

[0021] Furthermore, the molar ratio of dibutyltin dilaurate to ether oxygen type polymer is (0.005-0.007):1.

[0022] Furthermore, in step S2, the time of the primary reaction is 0.5 to 2 hours; in step S2, the time of the secondary polymerization reaction is 1 to 4 hours.

[0023] Furthermore, in step S1, the lithium-rich manganese-based positive electrode material is obtained by mixing a hydroxide precursor with a lithium source, calcining the mixture in a pure oxygen atmosphere, and then crushing and screening the mixture.

[0024] Furthermore, the chemical formula of the hydroxide precursor is Mn a Co b Ni c Zr d Nb e W f (OH)2, wherein the values ​​of a, b, c, d, e and f are 0.5≤a<1, 0≤b<0.5, 0≤c<0.5, 0≤d+e+f<0.02 respectively; the hydroxide precursor is prepared by coprecipitation method.

[0025] Furthermore, in step S1, the dispersion is ultrasonic dispersion or mechanical stirring dispersion.

[0026] In a third aspect, a lithium-ion battery is provided, comprising the aforementioned modified lithium-rich manganese-based positive electrode material or the modified lithium-rich manganese-based positive electrode material prepared by the aforementioned preparation method.

[0027] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects:

[0028] (1) Doping polyether polyurethane with lithium-rich manganese-based positive electrode materials can significantly improve the electronic conductivity of the materials, overcome the problem of irreversible loss of the first-cycle discharge capacity of lithium-rich manganese-based positive electrode materials, and stabilize the structure of the positive electrode materials, inhibit side reactions on the surface of the positive electrode materials in the electrolyte and the dissolution of transition metals, thereby improving the cycle performance of the battery.

[0029] (2) Multi-element synergistic doping is used in the precursor synthesis stage to effectively regulate the dominant growth of the active crystal plane (010) of the lithium-rich manganese-based positive electrode material, increase the number of lithium ion diffusion channels, and significantly improve the lithium ion diffusion rate of the lithium-rich manganese-based positive electrode material, thereby improving the electrochemical performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is the SEM image of the lithium-rich manganese-based positive electrode material prepared in Example 1.

[0032] Figure 2 HRTEM images of the (010) crystal plane of the lithium-rich manganese-based positive electrode materials prepared in Example 1 and Example 4.

[0033] Figure 3 This is a comparison chart of the rate performance of button cells assembled with lithium-rich manganese-based positive electrode materials prepared in Example 1 and Comparative Example 1.

[0034] Figure 4 This is a comparison chart of the first charge and discharge curves of button cells assembled with the lithium-rich manganese-based positive electrode materials prepared in Example 1 and Comparative Example 1.

[0035] Figure 5 It is a comparison chart of the cycle performance of lithium-ion batteries assembled with lithium-rich manganese-based positive electrode materials prepared in various embodiments and comparative examples at a 1C rate. DETAILED DESCRIPTION

[0036] In response to the technical problems of low electronic conductivity and low first coulombic efficiency of lithium-rich manganese-based positive electrode materials, the applicant has found through research that the polyether polyurethane obtained by polymerization of certain ether oxygen polymers, isocyanate organics and polyols to coat and modify the lithium-rich manganese-based positive electrode materials can not only improve the electronic conductivity of the positive electrode materials, improve the rate performance and first coulombic efficiency, but also stabilize the structure of the positive electrode materials, inhibit side reactions on the surface of the positive electrode materials in the electrolyte and the dissolution of transition metals, and improve the cycle performance of the battery.

[0037] The invention provides a modified lithium-rich manganese-based positive electrode material, comprising a lithium-rich manganese-based positive electrode material matrix and a polyether polyurethane layer on the surface of the lithium-rich manganese-based positive electrode material matrix.

[0038] In some preferred embodiments, the chemical formula of the lithium-rich manganese-based positive electrode material matrix is ​​xLi2MnO3·(1-x)LiMn a Co b Ni c Zr d Nb e Mo f O2, where 0<x<1, a+b+c+d+e+f=1, 0.5≤a<1, 0≤b<0.5, 0≤c<0.5, 0≤d+e+f<0.02. Doping and modifying lithium-rich manganese-based positive electrode materials with Nb, Zr and Mo is beneficial to improving their electrochemical performance.

[0039] In some preferred embodiments, the lithium-rich manganese-based positive electrode material matrix is ​​prepared by a hydroxide precursor Mn a Co b Ni c Zr d Nb e Mo f (OH)2 is mixed with lithium source and sintered. The hydroxide precursor Mn doped with Zr, Nb, and Mo is used. a Co b Ni c Zr d Nb e Mo f (OH)2 is used as a raw material to prepare the matrix of lithium-rich manganese-based positive electrode materials. The use of multi-element synergistic doping in the precursor synthesis stage can effectively regulate the dominant growth of the active crystal surface (010) of the lithium-rich manganese-based positive electrode material, broaden the lithium ion diffusion channel, and improve the lithium ion diffusion kinetics; in addition, due to the use of co-precipitation method to prepare the precursor Mn a Co b Ni c Zr d Nb e Mo f (OH)2 can effectively reduce the multi-phase coexistence phenomenon caused by the uneven distribution of elements inside the material, achieve relatively uniform element doping, and then fully and effectively play the doping role of multiple elements, improve the lithium ion diffusion kinetics, thereby optimizing the severe lithium concentration gradient from the inside to the outside, optimizing the lithium ion aggregation problem caused by lithium ion polarization, and increasing the lithium ion diffusion rate of lithium-rich manganese-based positive electrode materials, thereby improving the electrical properties of lithium-rich manganese-based positive electrode materials.

[0040] In some preferred embodiments, the polyether polyurethane layer is obtained by polymerizing a low molecular weight ether oxygen polymer, an isocyanate organic substance and a polyol.

[0041] In some preferred embodiments, the mass of the polyether polyurethane layer is 0.1% to 1.5% of the lithium-rich manganese-based positive electrode material matrix.

[0042] The present invention also provides a method for preparing a modified lithium-rich manganese-based positive electrode material, comprising:

[0043] S1, adding a lithium-rich manganese-based positive electrode material into an organic solvent and dispersing the material to obtain a dispersion;

[0044] S2. Add low molecular weight ether oxygen type polymer and isocyanate organic matter to the dispersion, add dibutyltin dilaurate catalyst after the added materials are dissolved, carry out a primary reaction, and then continue to add polyol to carry out a secondary polymerization reaction. After the reaction is completed, solid-liquid separation and drying are carried out to obtain a polyether polyurethane coated modified lithium manganese-rich positive electrode material.

[0045] In some embodiments, the low molecular weight ether oxygen type polymer is one or more of polytetrahydrofuran, polyethylene oxide, and polypropylene oxide.

[0046] In some embodiments, the isocyanate organic compound is one or more of hexamethylene diisocyanate, xylylene diisocyanate, and methylcyclohexylene diisocyanate.

[0047] In some embodiments, the polyol is one or more of glycerol, 1,4-butanediol, and pentaerythritol.

[0048] In some embodiments, the organic solvent is one of ether and acetone; the amount of the organic solvent can be conventionally determined according to demand.

[0049] In some preferred embodiments, the molar ratio of the low molecular weight ether oxygen type polymer, the isocyanate organic substance and the polyol is 1:(2.2-2.5):1.

[0050] In some preferred embodiments, the molar ratio of dibutyltin dilaurate to ether oxygen type polymer is (0.005-0.007):1.

[0051] In some preferred embodiments, in step S2, the time of the primary reaction is 0.5 to 2 hours.

[0052] In some preferred embodiments, in step S2, the secondary polymerization reaction time is 1 to 4 hours.

[0053] In some preferred embodiments, in step S1, the lithium-rich manganese-based positive electrode material is obtained by mixing a hydroxide precursor with a lithium source, calcining in a pure oxygen atmosphere, and then crushing and screening.

[0054] The lithium source can be lithium oxide or conventional lithium salt prepared from lithium ion positive electrode materials, for example, one or more of lithium oxide, lithium hydroxide, lithium carbonate, and lithium acetate. The amount of lithium salt added can be determined according to the conventional amount required for the preparation of lithium-rich manganese-based positive electrode materials, for example, the molar ratio of lithium to precursor can be in the range of 1.23 to 3.

[0055] The sintering may adopt the conventional sintering mechanism in the art for preparing lithium-rich manganese-based positive electrode materials, for example, the material may be pretreated at 400-500° C. for 3-6 hours, then heated to 700-1000° C. and kept warm for 12-30 hours.

[0056] In some preferred embodiments, the chemical formula of the hydroxide precursor is Mn a Co b Ni c Zr d Nb e Mo f (OH)2, wherein the values ​​of a, b, c, d, e and f are 0.5≤a<1, 0≤b<0.5, 0≤c<0.5, 0≤d+e+f<0.02, a+b+c+d+e+f=1; the hydroxide precursor is prepared by a co-precipitation method.

[0057] The coprecipitation method for preparing the hydroxide precursor specifically includes:

[0058] (1) uniformly stirring and mixing a soluble nickel salt, a soluble manganese salt, a soluble cobalt salt, and an optionally added soluble zirconium compound, an optionally added soluble niobium compound, and an optionally added soluble tungsten compound in deionized water according to a certain stoichiometric ratio to prepare a metal salt solution;

[0059] (2) The prepared metal salt solution, ammonia water and alkaline solution are introduced into the reaction kettle in parallel, and a coprecipitation reaction is carried out under heat preservation and stirring;

[0060] (3) After the co-precipitation reaction is completed, the precursor slurry is taken out, and the residual sodium and sulfur in the precursor slurry is washed away with a hot alkaline solution, and then rinsed with pure water, dried, and finally sieved to obtain a precursor of a lithium-rich manganese-based positive electrode material.

[0061] The preparation of hydroxide precursors by co-precipitation is a conventional method for preparing hydroxide precursors in the art, and various process parameters can be conventionally adjusted according to the elements to be co-precipitated.

[0062] In step (2), the pH of the coprecipitation reaction can be conventionally regulated according to the precipitation pH of each metal element. In some implementations, the pH value of the reaction system is 9-12; the temperature of the coprecipitation reaction is the conventional coprecipitation temperature in the art, and the coprecipitation reaction temperature is 30-100°C; the coprecipitation reaction time can be conventionally determined according to the material dosage and feed rate. In some implementations, the reaction time is 10-24h.

[0063] In step (1), the soluble nickel salt may be a conventional soluble nickel salt in the art, for example, one or more of nickel nitrate, nickel acetate, nickel chloride and nickel sulfate; the soluble manganese salt may be a conventional soluble manganese salt in the art, for example, one or more of manganese nitrate, manganese acetate, manganese chloride and manganese sulfate; the soluble zirconium compound may be a conventional soluble zirconium compound in the art, for example, zirconium nitrate; the niobium compound is niobium oxalate; and the molybdenum compound is molybdenum acetate.

[0064] In step (1), the metal cation concentration in the metal salt solution may be 0.05 mol / L to 1.5 mol / L. In addition, the total molar amount of zirconium, niobium and molybdenum in the metal salt solution accounts for no more than 2% of the total molar amount of metal elements.

[0065] In step (1), the alkaline solution is an aqueous solution of one or more of sodium hydroxide and potassium hydroxide; the hydroxide concentration in the alkaline solution may be 0.5 mol / L to 8 mol / L.

[0066] In step (1), the concentration of the ammonia water can adopt the conventional ammonia water concentration in the art, for example, it can be 0.5 mol / L, 1 mol / L, 2 mol / L, etc.

[0067] In step (3), the hot alkaline solution is a hot solution of one or more of sodium hydroxide and potassium hydroxide; the use of hot alkaline solution can effectively improve the elution effect of sodium sulfate impurities, and specifically, the temperature of the hot alkaline solution can be 40-100° C. In step (3), the pure water used for washing can also be hot water to improve the washing effect, and the temperature of the pure water can be 40-100° C.

[0068] In step (3), the drying temperature and time can be determined according to conventional requirements, as long as the moisture in the material can be removed well; for example, the oven drying temperature can be 60-140°C, and the drying time can be 4-20 hours.

[0069] In some preferred embodiments, in step S1, the dispersion is ultrasonic dispersion or mechanical stirring dispersion. The process parameters of ultrasonic dispersion or mechanical stirring dispersion can be conventionally determined according to the desired dispersion effect.

[0070] Some embodiments of the present invention also provide a lithium-ion battery, comprising the aforementioned modified lithium-rich manganese-based positive electrode material or the modified lithium-rich manganese-based positive electrode material prepared by the aforementioned preparation method.

[0071] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0072] Example 1

[0073] (1) Weigh 2mol NiSO4·6H2O, 2mol CoSO4·7H2O, 6mol MnSO4·H2O, 0.05mol Mo(NO3)2, 0.05mol Zr(SO4)2⋅4H2O, 0.05mol C 10 H5B 20 Prepare 2L mixed metal salt solution; weigh 5mol sodium hydroxide to prepare 2L solution as precipitant; use a concentration of 0.5mol L -1 of ammonia as a complexing agent.

[0074] (2) The mixed metal salt solution, precipitant and complexing agent are simultaneously introduced into a continuous stirred tank reactor for a coprecipitation reaction at a rate of 100 mL h -1 The mixed metal salt solution was pumped into the reaction system at a speed of 10 to 11. During the reaction, the pH value of the reaction system was adjusted to about 10 to 11, the reaction temperature was adjusted to 60°C, the stirring speed in the continuous stirred tank reactor was adjusted to 500 rpm, and the reaction was carried out for 16 hours.

[0075] (3) After the reaction is completed, the obtained precipitate is repeatedly washed with deionized water and then dried in an oven at 80°C. After being sieved with a 500-mesh sieve, it becomes the precursor of the target positive electrode material.

[0076] (4) Take 0.1 mol of the precursor and mix it with 0.065 mol of Li2CO3 and then sinter it in a muffle furnace. Sinter the mixture in an air environment at 450°C for 5 hours and then sinter it at 800°C for 15 hours. After the reaction is completed, take it out, grind it, and sieve it to obtain the target positive electrode material.

[0077] (5) Take 0.1 mol of the positive electrode material and ultrasonically disperse it in acetone for 10 minutes. After uniform dispersion, the dispersion is obtained, and the dispersion is placed in a nitrogen-filled glove box for subsequent polymerization reaction. The subsequent polymerization reaction includes: adding 1 mmol of polytetrahydrofuran and 2.4 mmol of xylene diisocyanate to the dispersion under continuous stirring, and after uniform dissolution, adding 6 μmol of catalyst dibutyltin dilaurate to carry out a primary polymerization reaction. After the reaction lasts for 1 hour, 1 mmol of propylene glycol is continuously added to carry out a secondary polymerization reaction. After the reaction lasts for 2 hours, the dispersion is placed in a vacuum drying oven and dried at 70°C for 36 hours to obtain a polyether polyurethane-coated lithium-rich manganese-based positive electrode material.

[0078] The SEM image of the modified cathode material is shown in Figure 1 As shown, the TEM image of the modified cathode material is as follows Figure 2 (a) shown.

[0079] Comparative Example 1

[0080] The only difference between this comparative example and Example 1 is that the coating modification step (5) is omitted.

[0081] Example 2

[0082] (1) Weigh 2mol NiSO4·6H2O, 2mol CoSO4·7H2O, 6mol MnSO4·H2O, 0.01mol Mo(NO3)2, 0.01mol Zr(SO4)2⋅4H2O, 0.01mol C 10 H5B 20 Prepare 2L mixed metal salt solution; weigh 5mol sodium hydroxide to prepare 2L solution as precipitant; -1 of ammonia as a complexing agent.

[0083] (2) The mixed metal salt solution, precipitant and complexing agent are simultaneously introduced into a continuous stirred tank reactor for a coprecipitation reaction at a rate of 100 mL h -1 The mixed metal salt solution was pumped into the reaction system at a speed of 10 to 11. During the reaction, the pH value of the reaction system was adjusted to about 10 to 11, the reaction temperature was adjusted to 60°C, the stirring speed in the continuous stirred tank reactor was adjusted to 500 rpm, and the reaction was carried out for 10 hours.

[0084] (3) After the reaction is completed, the obtained precipitate is repeatedly washed with deionized water and then dried in an oven at 80°C. After being sieved with a 500-mesh sieve, it becomes the precursor of the target positive electrode material.

[0085] (4) Take 0.1 mol of the precursor and mix it with 0.065 mol of Li2O and then sinter it in a muffle furnace. Sinter the mixture in an air environment at 500°C for 3 hours and then sinter it at 1000°C for 12 hours. After the reaction is completed, take it out, grind it, and sieve it to obtain the target positive electrode material.

[0086] (5) Take 0.1 mol of the positive electrode material, ultrasonically disperse it in ether for 10 minutes to obtain a dispersion, and after uniform dispersion, place it in a nitrogen-filled glove box for subsequent polymerization reaction. The subsequent polymerization reaction includes: adding 0.1 mmol of polyethylene oxide and 0.22 mmol of hexamethylene diisocyanate to the dispersion under continuous stirring, and after uniform dissolution, adding 0.5 μmol of catalyst dibutyltin dilaurate (DBTDL) to carry out a primary polymerization reaction. After the reaction lasts for 0.5 hours, 0.1 mmol of 1.4-butanediol is then added to carry out a secondary polymerization reaction. After the reaction lasts for 1 hour, it is placed in a vacuum drying oven and dried at 60°C for 56 hours to obtain a polyether polyurethane-coated lithium-rich manganese-based positive electrode material.

[0087] Example 3

[0088] (1) Weigh 2mol NiSO4·6H2O, 2mol CoSO4·7H2O, 6mol MnSO4·H2O, 0.067mol Mo(NO3)2, 0.067mol Zr(SO4)2⋅4H2O, 0.067mol C 10 H5B 20 Prepare 2L mixed metal salt solution; weigh 5mol sodium hydroxide to prepare 2L solution as precipitant; -1 of ammonia as a complexing agent.

[0089] (2) The mixed metal salt solution, precipitant and complexing agent are simultaneously introduced into a continuous stirred tank reactor for a coprecipitation reaction at a rate of 100 mL h -1 The mixed metal salt solution was pumped into the reactor at a speed of 1000 rpm. During the reaction, the pH value of the reaction system was adjusted to about 10-11, and the reaction temperature was adjusted to 60° C. In addition, the stirring speed in the continuous stirred tank reactor was adjusted to 500 rpm, and the reaction was continued for 24 hours.

[0090] (3) After the reaction is completed, the obtained precipitate is repeatedly washed with deionized water and then dried in an oven at 80°C. After being sieved with a 500-mesh sieve, it becomes the precursor of the target positive electrode material.

[0091] (4) 0.1 mol of the precursor was mixed with 0.14 mol of LiOH and then sintered in a muffle furnace. The mixture was sintered in an air environment at 400°C for 6 h and then sintered at 700°C for 30 h. After the reaction was completed, the mixture was taken out, ground, and sieved to obtain the target positive electrode material.

[0092] (5) Take 0.1 mol of the positive electrode material, ultrasonically disperse it in ether for 10 minutes to obtain a dispersion, and after uniform dispersion, place it in a nitrogen-filled glove box for subsequent polymerization reaction. The subsequent polymerization reaction includes: adding 1.5 mmol of polyoxypropylene and 3.75 mmol of methylcyclohexylene diisocyanate to the dispersion under continuous stirring, and after uniform dissolution, adding 10.5 μmol of catalyst dibutyltin dilaurate (DBTDL) to carry out a primary polymerization reaction. After reacting for 2 hours, 1.5 mmol of pentaerythritol is then added to carry out a secondary polymerization reaction. After reacting for 4 hours, it is placed in a vacuum drying oven and dried at 100°C for 24 hours to obtain a polyether polyurethane-coated lithium-rich manganese-based positive electrode material.

[0093] Example 4

[0094] (1) Weigh 2 mol NiSO4·6H2O, 2 mol CoSO4·7H2O, and 6 mol MnSO4·H2O to prepare 2 L of mixed metal salt solution; weigh 5 mol sodium hydroxide to prepare 2 L of solution as a precipitant; use a concentration of 0.5 mol L -1 of ammonia as a complexing agent.

[0095] (2) The mixed metal salt solution, precipitant and complexing agent are simultaneously introduced into a continuous stirred tank reactor for a coprecipitation reaction at a rate of 100 mL h -1 The mixed metal salt solution was pumped into the reaction system at a speed of 10 to 11. During the reaction, the pH value of the reaction system was adjusted to about 10 to 11, the reaction temperature was adjusted to 60°C, the stirring speed in the continuous stirred tank reactor was adjusted to 500 rpm, and the reaction was carried out for 16 hours.

[0096] (3) After the reaction is completed, the obtained precipitate is repeatedly washed with deionized water and then dried in an oven at 80°C. After being sieved with a 500-mesh sieve, it becomes the precursor of the target positive electrode material.

[0097] (4) Take 0.1 mol of the precursor and mix it with 0.065 mol of Li2CO3 and then sinter it in a muffle furnace. Sinter the mixture in an air environment at 450°C for 5 hours and then sinter it at 800°C for 15 hours. After the reaction is completed, take it out, grind it, and sieve it to obtain the target positive electrode material.

[0098] (5) Take 0.1 mol of positive electrode material and ultrasonically disperse it in acetone for 10 minutes. After uniform dispersion, a dispersion is obtained, which is placed in a nitrogen-filled glove box for subsequent polymerization reaction. The subsequent polymerization reaction includes: adding 1 mmol of polytetrahydrofuran and 2.4 mmol of xylene diisocyanate to the dispersion under continuous stirring. After uniform dissolution, 6 μmol of catalyst dibutyltin dilaurate is added to carry out a primary polymerization reaction. After the reaction lasts for 1 hour, 1 mmol of propylene glycol is added to carry out a secondary polymerization reaction. After the reaction lasts for 2 hours, it is placed in a vacuum drying oven and dried at 70°C for 36 hours to obtain a polyether polyurethane-coated lithium-manganese-based positive electrode material. The TEM image of the obtained modified positive electrode material is shown in the figure. Figure 2 (b) shown.

[0099] Comparison of the HRTEM images of the (010) crystal plane of the undoped (Example 4) and doped (Example 1) lithium-rich manganese-based materials ( Figure 2 ),from Figure 2 It can be clearly seen that the lattice spacing of the (010) crystal plane near the surface of the doped lithium-rich manganese-based material is clearer, the lattice fringes are longer and smoother, and the area of ​​the (010) crystal plane accounts for a larger proportion. Therefore, it can be fully proved that Zr, Nb, and Mo doping can further enhance the dominant growth of the (010) crystal plane, thereby broadening the lithium ion diffusion channel and improving the lithium ion diffusion kinetics.

[0100] The lithium-rich manganese-based lithium battery materials prepared in each embodiment and comparative example are assembled into batteries by the following method:

[0101] The lithium-rich manganese-based lithium battery material was used as the positive electrode material, and was mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as the solvent. The mixture was placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a slurry. The slurry was coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h, punched into a pole piece with a diameter of 12mm, and then dried at 105°C in a vacuum drying oven for 4h. It was placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm for 4h to reduce the moisture adsorbed by the pole piece during the transfer process, and then assembled into a CR2032 button battery in the glove box. The battery uses a pure metal lithium sheet with a diameter of 16 mm and a thickness of 0.5 mm as the negative electrode, and a porous polyethylene membrane of model Celgard2300 with a diameter of 18 mm as the separator.

[0102] After the battery is assembled and aged for 12 hours, charge and discharge tests at different potentials are performed.

[0103] The rate performance of the lithium ion battery assembled with the positive electrode materials obtained in Example 1 and Comparative Example 1 is as follows: Figure 3 As shown, the first charge and discharge curve is as follows Figure 4 As shown. Figure 3 It can be seen that after the positive electrode material is coated and modified, the rate performance of the battery is significantly improved. The reason for this may be that the polyether polyurethane layer can effectively improve the electronic conductivity, thereby improving the electrical properties of the material. Figure 4 It can be seen that after the positive electrode material is coated and modified, the initial charge and discharge efficiency of the battery is also improved, indicating that the polyether polyurethane coating modification effectively improves the structural reversibility of the material, and the voltage platform in Example 1 is also higher than that in Comparative Example 1, indicating that the coating effectively improves the voltage platform of the lithium-rich manganese-based material.

[0104] The button cells assembled with the positive electrode materials prepared in the embodiments and comparative examples were activated for 2 cycles at a voltage of 2-4.8 V and a current density of 0.1 C, and then cycled for 100 cycles at a current density of 1 C.

[0105] The cycle performance of the battery assembled with the positive electrode materials prepared in each embodiment and comparative example at 1C is shown in the figure Figure 5 As shown, from Figure 5 It can be seen that the specific capacities of the batteries assembled with the positive electrode materials prepared in each embodiment and comparative example 1 are not much different when activated. However, after a long cycle, the specific capacity of the battery corresponding to comparative example 1 drops sharply, and the capacity retention rate is the lowest, indicating that irreversible changes have occurred in its lithium-rich structure.

[0106] The capacity retention rate of the battery assembled with the positive electrode material coated with polyether polyurethane is generally high. When the coating amount is 1%, the capacity retention rate reaches the highest, which is 97.3%. This shows that the polyether polyurethane layer coating significantly improves the cycle performance. After analysis, this may be because the polyether polyurethane stabilizes the structure of the lithium-rich positive electrode material, inhibits the side reaction and transition metal dissolution on the surface of the positive electrode material in the electrolyte, and thus improves the cycle performance of the battery.

[0107] Under the condition that the main material in Example 4 is not doped with Zr, Nb, or Mo, the rate capacity of the lithium-rich manganese-based material is low, which proves that doping can effectively increase the lithium ion diffusion rate inside the material structure and effectively increase the rate capacity of the material. Moreover, the undoped and only coated lithium-rich manganese-based material shows a better capacity retention rate than the battery assembled with the lithium-rich manganese-based material not coated with polyether polyurethane, which further proves the beneficial effect of polyether polyurethane coating.

[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a modified lithium-rich manganese-based positive electrode material, characterized in that: include: S1, adding a lithium-rich manganese-based positive electrode material into an organic solvent and dispersing the material to obtain a dispersion; S2, adding a low molecular weight ether oxygen type polymer and an isocyanate organic substance to the dispersion, adding a catalyst dibutyltin dilaurate after the added materials are dissolved, and performing a primary reaction, wherein the primary reaction time is 0.5 to 2 hours, and then continuing to add a polyol to perform a secondary polymerization reaction, wherein the secondary polymerization reaction time is 1 to 4 hours, and after the reaction is completed, solid-liquid separation and drying are performed to obtain a polyether polyurethane coated modified lithium manganese-rich positive electrode material; The low molecular weight ether oxygen type polymer is polytetrahydrofuran; The isocyanate organic substance is xylylene diisocyanate; The polyol is glycerol; The molar ratio of dibutyltin dilaurate to ether oxygen type polymer is (0.005-0.007):

1.

2. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The organic solvent is one of ether and acetone.

3. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1 or 2, characterized in that: The molar ratio of the low molecular weight ether oxygen type polymer, the isocyanate organic matter and the polyol is 1:(2.2-2.5):

1.

4. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step S1, the lithium-rich manganese-based positive electrode material is obtained by mixing a hydroxide precursor with a lithium source, calcining in a pure oxygen atmosphere, and then crushing and screening.

5. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: The chemical formula of the hydroxide precursor is Mn a Co b Ni c Zr d Nb e W f (OH)2, wherein the values ​​of a, b, c, d, e and f are 0.5≤a<1, 0≤b<0.5, 0≤c<0.5, 0≤d+e+f<0.02, a+b+c+d+e+f=1; the hydroxide precursor is prepared by a co-precipitation method.

6. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step S1, the dispersion is ultrasonic dispersion or mechanical stirring dispersion.

7. Modified lithium-rich manganese-based positive electrode material, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. The modified lithium-rich manganese-based positive electrode material according to claim 7, characterized in that: The mass of the polyether polyurethane layer is 0.1% to 1.5% of the lithium-rich manganese-based positive electrode material matrix.

9. A lithium-ion battery, characterized in that Comprising the modified lithium-rich manganese-based positive electrode material as described in claim 7 or 8.